2016
DOI: 10.1111/jfpp.12715
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Texture and Quality of Minimally Processed Litchi Fruit Using Various Calcium Salts

Abstract: The efficacies of three calcium salts at different concentrations (0.5–3%) and temperatures (4, 25 and 50C) were studied to improve texture and quality of litchi arils cv. “Jugkapat.” A peroxyacetic acid was used as sanitizer in pre‐ (100 mg/L, 3 min) and post‐deseeding steps (50 mg/L, 1 min). The arils were immersed in 1% calcium chloride, 2% calcium propionate at 25C and 2% calcium lactate at 50C had the best firmness. All calcium salts decreased the respiration rate by 1.5 to 2 folds, reduced juice leakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several studies have been reported on the minimal processing and pre-treatments of different varieties of litchi to preserve and prolong their shelf life (Bolaños et al, 2010;Dong et al, 2004;Nath, 2006, 2008;Kaushik et al, 2014;Phanumong et al, 2015Phanumong et al, , 2017Phanumong et al, 2016). The application of dilute hypochlorite have been confirmed to be beneficial in prolonging the shelf life of fresh-cut tissues (Ayhan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the minimal processing and pre-treatments of different varieties of litchi to preserve and prolong their shelf life (Bolaños et al, 2010;Dong et al, 2004;Nath, 2006, 2008;Kaushik et al, 2014;Phanumong et al, 2015Phanumong et al, , 2017Phanumong et al, 2016). The application of dilute hypochlorite have been confirmed to be beneficial in prolonging the shelf life of fresh-cut tissues (Ayhan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, the excess calcium addition is required to keep the firmness of the product; therefore, it is pivotal to evaluate the application of calcium salts (acetate and lactate) on different cultivars of olives. However, conflicting evidence on the usefulness of various calcium salts in delaying the softening of fruits and vegetables has been recorded; firmness was higher in lychee fruit, fresh-cut carrot, and mango treated with CaCl 2 compared to treatment with calcium lactate [19][20][21][22][23], but fresh-cut melon showed the reverse effect [24], and canned peaches and fresh-cut cantaloupe showed no changes [22,24]. One of the primary disadvantages of calcium salts, particularly CaCl 2 , is that excessive quantities can give bitterness to food [22].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of calcium in tissue firmness is due to its ability to strengthen the cell wall by binding free carboxylic group of the pectin chains forming crosslinks or bridges and at the same time preserving the structural and functional integrity of membranes [17]. Different calcium salts, such as calcium lactate, calcium chloride, 2 Journal of Food Quality calcium phosphate, calcium propionate, and calcium gluconate, have been used in food industry for preserving and/or enhancing of the product firmness [18][19][20]. Calcium chloride has been widely used as preservative and firming agent in the fruit and vegetable processing industry for whole and fresh-cut commodities, but the use of calcium chloride has also been associated with bitterness and off-flavors [21].…”
Section: Introductionmentioning
confidence: 99%